Atrial edema in patients with atrial fibrillation with chronic heart failure. (24th May 2021) - Kirillova, VV; Mochula, OV; Garganeeva, AA; Usov, VYU; Batalov, RE; Meshchaninov, VN; Popov, SV
Abstract: Funding Acknowledgements: Type of funding sources: None. Objective: to investigate the intensity of the atrial septum by T2-weighted magnetic resonance imaging (MRI) in patients with chronic heart failure (CHF), with and without atrial fibrillation (AF). Materials and methods. In patients with CHF with atrial fibrillation (n = 23, including 11 patients with paroxysmal form, and 12 patients with constant forms) and without (n = 9) of arrhythmias in the control group – almost healthy (n = 6) we evaluated the signal intensity (SI) of the interatrial septum, the interventricular septum, and skeletal muscle at MRI T-2 weighted images. An increase in the value of SI in 2 times or more compared with the SI of skeletal muscle was regarded as an MRI signs of myocardial edema. Results. The SI of the atrial septum in patients with CHF who have constant forms of atrial fibrillation is higher than in the control (2775.58 ± 383.61 relative to the control - 1448.57 ± 291.30, p < 0.05). The MPP gain index in patients with paroxysmal AF equal to 1.59 ± 0.10 did not differ in comparison with patients with CHF who do not have rhythm disorders - 1.53 ± 0.12. An index of atrial septal enhancement greater than 2, indicating the presence of MRI signs of atrial septal myocardial edema  was detected only in patients with a constant form of AF (2.39 ± 0.18) than in patients with CHF with paroxysmal AF, in patients with CHF without rhythm disturbances and in the control group (1.59 ± 0.23; 1.53 ± 0.28 and 1.15 ± 0.16, respectively,  p < 0.05). Summary. In patients with CHF who have a constant form of atrial fibrillation, according to T2-weighted MRI images, signs of edema of the myocardium of the atrial septum were revealed in comparison with the control group and patients with CHF who have a paroxysmal form of atrial fibrillation and without rhythm disturbances.